2018
DOI: 10.1155/2018/1542520
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density L-Shaped Backscattering Chipless Tag for RFID Bistatic Systems

Abstract: Chipless radiofrequency identification (RFID) technology is very promising for sensing, identification, and tracking for future Internet of Things (IoT) systems and applications. In this paper, we propose and demonstrate a compact 18-bit, dual polarized chipless RFID tag. The proposed tag is based on L-shaped resonators designed so as to maximize the spectral and spatial encoding capacities. The proposed RFID tag operates an over 4 GHz frequency band (i.e., 6.5 GHz to 10.5 GHz). The tag is simulated, fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The cost of RFID devices is mainly dependent on the tags, which is the cost of chips. Thus, many efforts have been made to develop chipless RFID, and some sensors based on chipless RFID technology have been developed [34,35,36,37,38,39,40]. These chipless sensors show not only low cost but also high reliability even if these sensors work in harsh environment.…”
Section: Design Of Nfc Antennasmentioning
confidence: 99%
“…The cost of RFID devices is mainly dependent on the tags, which is the cost of chips. Thus, many efforts have been made to develop chipless RFID, and some sensors based on chipless RFID technology have been developed [34,35,36,37,38,39,40]. These chipless sensors show not only low cost but also high reliability even if these sensors work in harsh environment.…”
Section: Design Of Nfc Antennasmentioning
confidence: 99%
“…Several topologies relating to those used based on resonators have been suggested for chipless tags. Such topologies include circular loop [ 20 , 21 , 22 ], square loop [ 23 , 24 , 25 ], U-shaped [ 26 , 27 , 28 ], C-shaped [ 29 , 30 ], L-shaped [ 31 , 32 , 33 , 34 ], slotted [ 34 , 35 , 36 ], rhombic [ 37 , 38 ], octagonal [ 39 ], and microstrip-line [ 18 , 40 , 41 ]. It is also worth noting that the authors have suggested textile wearable application technology devices in the literature [ 42 , 43 ], which can be used as chipless RFID sensor tags in identification and tracking applications.…”
Section: Introductionmentioning
confidence: 99%
“…The read range is a few centimeters for the frequency-coded tags (<1 m) or up to 2–3 m for the time-domain-coded tags [ 21 ]. Several studies [ 20 , 22 , 23 , 24 ] focused on increasing the number of bits to encode in order to compete in cost with chip-based competitive technologies (HF or UHF). The number of bits depends on the frequency bandwidth; thus, chipless RFID is usually designed at ultra-wideband (UWB, 3.1–10.6 GHz).…”
Section: Introductionmentioning
confidence: 99%